Formulation and Evaluation of Ointment Preparations with Nutgrass Extract (Cyperus rotundus L.) Using Different Ointment Bases - Yusfia Urwatul Wutsqa; Abdul Munif; Dwi Retno Sari (JURNAL FARMASI DAN MAKANAN, 2023)
Nutgrass (Cyperus rotundus L.) is a medicinal plant that belongs to the Cyperaceae family. Nutgrass (Cyperus rotundus L.) is often used as a remedy to treat diseases caused by bacterial activity such as skin itching, boils, and vaginal discharge. The aim of this research is to determine the physical properties of the ointment containing nutgrass extract (Cyperus rotundus L.). Nutgrass (Cyperus rotundus L.) is extracted using 70% ethanol solvent and then formulated into ointments with different concentrations of hydrocarbon and absorbent bases. The ointment preparations made consist of three formulations with extract concentrations of 20%, 30%, and 40% to allow for comparison. The evaluation tests for the ointment preparations containing nutgrass extract (Cyperus rotundus L.) include organoleptic tests, homogeneity tests, pH tests, spreadability tests, adhesion tests, and stability tests. The analysis method used in this research is descriptive, which involves describing the results of the formulations of ointment preparations with nutgrass extract (Cyperus rotundus L.). The research results indicate that ethanol extract can be formulated into ointment preparations, and there are several tests that meet the evaluation criteria, namely organoleptic tests, adhesion tests, and homogeneity tests.